Increased airport security and the adjoining areas - Васюхін, М.І.; Гулевець, В.Д.; Головко, Б.Б. (Proceedings of National Aviation University (archive), 2009)
Methods and facilities of realization of construction of the first turn of the integrated geoinformation system of complex defense of airport and adjoining to him areas are presented in work. Analysis of results of its exploitation in the conditions of airport of city Budapest allowed to propose the ways of problem decision of security level increasing of airport security as an especially important object.